2011
DOI: 10.1002/jmri.22605
|View full text |Cite
|
Sign up to set email alerts
|

Supine breast MRI

Abstract: Purpose: To achieve high-quality unilateral supine breast magnetic resonance imaging (MRI) as a step to facilitate image aiding of clinical applications, which are often performed in the supine position. Contrastenhanced breast MRI is a powerful tool for the diagnosis of cancer. However, prone patient positioning typically used for breast MRI hinders its use for image aiding. Materials and Methods:A fixture and a flexible four-element receive coil were designed for patient-specific shaping and placement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 21 publications
(18 reference statements)
0
27
0
Order By: Relevance
“…5 recent investigations have demonstrated feasibility [16]. MRI is non-ionizing, unlike CT, and could enable additional imaging throughout the patients treatment in future, to improve accuracy without exposing the patient to further ionising radiation.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…5 recent investigations have demonstrated feasibility [16]. MRI is non-ionizing, unlike CT, and could enable additional imaging throughout the patients treatment in future, to improve accuracy without exposing the patient to further ionising radiation.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…3). Siegler et al [33] showed that supine breast MRI resulted in comparable image quality as regular diagnostic MRI. Positioning on a radiotherapy wedge support may be feasible particularly in wide-bore MRI scanners that are now commercially available.…”
Section: Technical Challenges For the Use Of Mri For Rt Dose Paintingmentioning
confidence: 99%
“…The one patient with discomfort and hence motion‐derived artifacts was in her 30 th week of pregnancy, the most advanced pregnancy of the cohort. Therefore, for patients in advanced pregnancy, supine examination using a thoracic coil or supine‐designed breast coil might be a proper alternative, although in this pilot study these were not attempted.…”
Section: Discussionmentioning
confidence: 99%